Forms of Knowledge in Early Modern Asia : Explorations in the Intellectual History of India and Tibet, 1500-1800 - Pollock, Sheldon I. (Book collections on Project MUSE., 2011)
Fills a gap in scholarship on Indian culture and power between 1500 and 1800, arguing that we can't know how colonialism changed South Asia unless we know what there was to be changed.